Local Generalized Symmetries and Locally Symmetric Parabolic Geometries - Gregorovič, J.; Zalabová, L. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
We investigate (local) automorphisms of parabolic geometries that generalize geodesic symmetries. We show that many types of parabolic geometries admit at most one generalized geodesic symmetry at a point with non-zero harmonic curvature. Moreover, we show that if there is exactly one symmetry at each point, then the parabolic geometry is a generalization of an affine (locally) symmetric space.